2017
DOI: 10.22159/ijpps.2017v9i6.16036
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia Lead to Transmural Inflammation of Colon and Increase Severity of Disease in Acetic Acid-Induced Colitis in Rat

Abstract: Objective: The present study was designed to evaluate the effect of hyperhomocysteinemia (Hhcy) induced by feeding rats high methionine diet on the colon wall. Colonic damages caused by Hhcy were compared with those induced by acetic -acid induced colitis.Methods: Sprague-Dawley rats (200-250g) were divided into four groups: group C (control), group M (received 1 g/kg methionine p. o. during 15 d), group A (colitis was induced by transrectal administration of acetic acid 4% on 8 th day) and group MA (received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…These data suggest that the morphometry changes detected could be, at least in part, explained by hyperhomocysteinemia. Hyperhomocysteinemia has been suggested to be a mediator of the inflammatory response in a rat experimental model of colitis induced by acetic acid [35]. The results from this study showed significant tissue damage and immune cell infiltration in all layers of the colon wall, indicating that HHcy is a significant toxic factor for colon tissues.…”
Section: Discussionmentioning
confidence: 54%
“…These data suggest that the morphometry changes detected could be, at least in part, explained by hyperhomocysteinemia. Hyperhomocysteinemia has been suggested to be a mediator of the inflammatory response in a rat experimental model of colitis induced by acetic acid [35]. The results from this study showed significant tissue damage and immune cell infiltration in all layers of the colon wall, indicating that HHcy is a significant toxic factor for colon tissues.…”
Section: Discussionmentioning
confidence: 54%